A Comprehensive Analysis of the Risk Factors for Postoperative Pancreatic Fistula Formation after Pancreaticoduodenectomy - Tanvi Y., Orion P (Academic Journal of Clinicians, 2025)
Background Postoperative pancreatic fistula (POPF) is a significant complication following pancreaticoduodenectomy (PD), impacting patient recovery and outcomes. Identifying risk factors for POPF formation is crucial for improving surgical strategies and patient management. Objective This study aims to analyze the risk factors contributing to the development of POPF in patients undergoing pancreaticoduodenectomy. Methods A retrospective cohort study was conducted involving 300 patients who underwent PD between 2015 and 2022. Data on demographic characteristics, preoperative comorbidities, intraoperative variables, and postoperative outcomes were collected. The occurrence of POPF was classified according to the International Study Group of Pancreatic Fistula (ISGPF) criteria. Multivariate logistic regression analysis was employed to identify independent risk factors associated with POPF. Results The overall incidence of POPF was 30%. Significant risk factors identified included elevated preoperative serum bilirubin levels (OR 2.5, p < 0.01), pancreatic duct diameter <3 mm (OR 3.1, p < 0.01), and intraoperative blood loss >200 mL (OR 2.2, p < 0.05). Additionally, patients with a history of pancreatitis had a higher likelihood of developing POPF (OR 1.8, p < 0.05). Conclusions Elevated bilirubin levels, small pancreatic duct diameter, significant intraoperative blood loss, and a history of pancreatitis are key risk factors for postoperative pancreatic fistula formation following pancreaticoduodenectomy. These findings can guide preoperative assessments and surgical decision-making to reduce POPF rates.